Highly specific sophorose β-glucosidase from Sphingomonas elodea ATCC 31461 for the efficient conversion of stevioside to rubusoside. (15th October 2019) - Lan, Qing; Tang, Tingting; Yin, Yu; Qu, XiaoYi; Wang, Zilong; Pang, Hao; Huang, Ribo; Du, Liqin
Highlights: This provides a special enzyme to target the diterpenoid compounds and sophorose. The enzyme show high activity toward stevioside. An enzymatic method is suitable for monitoring the content of stevioside. It is a fast and sensitive stevioside determination method. Abstract: Enzyme specificity and particularity is needed not only in enzymatic separation methods, but also in enzymatic determination methods for plant compound extraction. Stevioside, rubusoside, and rebaudioside A are natural sweet compounds from plants. These compounds have the same skeleton and only contain different side-chain glucosyl groups, making them difficult to separate. However, enzymes that target diterpenoid compounds and show specific activity for side-chain glucosyl groups are rare. Herein, we report the identification and characterization of an enzyme that can target both diterpenoid compounds and sophorose, namely, β-glucosidase SPBGL1 from Sphingomonas elodea ATCC 31461. SPBGL1 displayed high specificity toward sophorose, and activity toward stevioside, but not rebaudioside A. The stevioside conversion rate was 98%. SPBGL1 also operated at high substrate concentrations, such as in 50% crude steviol glycoside extract. Glucose liberated from stevioside was easy to quantify using the glucose oxidase method, allowing the stevioside content to be determined.